2009
DOI: 10.1152/ajpgi.90386.2008
|View full text |Cite
|
Sign up to set email alerts
|

HCl-activated neural and epithelial vanilloid receptors (TRPV1) in cat esophageal mucosa

Abstract: To test whether transient receptor potential channel vanilloid subfamily member-1 (TRPV1) mediates acid-induced inflammation in the esophagus, a tubular segment of esophageal mucosa was tied at both ends, forming a sac. The sac was filled with 0.01 N HCl (or Krebs buffer for control) and kept in oxygenated Krebs buffer at 37°C. The medium around the sac (supernatant) was collected after 3 h. Supernatant of the HCl-filled sac abolished contraction of esophageal circular muscle strips in response to electric fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 69 publications
6
65
0
Order By: Relevance
“…In keeping with this hypothesis, intra-esophageal capsaicin installation was found to induce symptoms of heartburn and chest pain in healthy volunteers (Kindt et al, 2009). The proposed role of TRPV1 is further supported by a recent study showing that acid-induced activation of TRPV1 receptors in feline esophageal mucosa results in substance P and CGRP release, presumably arising from submucous neurons, together with the release of platelet activating factor from esophageal epithelial cells, which also turned out to express TRPV1 (Cheng et al, 2009). The release of proinflammatory mediators via TRPV1 activation probably also plays a role in acid-induced esophagitis because TRPV1 null mice develop less severe esophagitis compared with wild-type mice (Fujino et al, 2006).…”
Section: Trpv Channelsmentioning
confidence: 73%
“…In keeping with this hypothesis, intra-esophageal capsaicin installation was found to induce symptoms of heartburn and chest pain in healthy volunteers (Kindt et al, 2009). The proposed role of TRPV1 is further supported by a recent study showing that acid-induced activation of TRPV1 receptors in feline esophageal mucosa results in substance P and CGRP release, presumably arising from submucous neurons, together with the release of platelet activating factor from esophageal epithelial cells, which also turned out to express TRPV1 (Cheng et al, 2009). The release of proinflammatory mediators via TRPV1 activation probably also plays a role in acid-induced esophagitis because TRPV1 null mice develop less severe esophagitis compared with wild-type mice (Fujino et al, 2006).…”
Section: Trpv Channelsmentioning
confidence: 73%
“…We demonstrated that, in these cells, PAF production is directly linked to TRPV1 activation, resulting in increased intracellular Ca 2ϩ , activation of a p38-dependent transduction pathway, and production of PAF (27). The production of SP and CGRP in the mucosa, however, was not affected by the PAF receptor antagonist CV-3988, indicating that production of SP and CGRP by submucosal neurons does not depend on PAF release from epithelial cells (14).…”
mentioning
confidence: 86%
“…We demonstrated that, in these cells, PAF production is directly linked to TRPV1 activation, resulting in increased intracellular Ca 2ϩ , activation of a p38-dependent transduction pathway, and production of PAF (27). The production of SP and CGRP in the mucosa, however, was not affected by the PAF receptor antagonist CV-3988, indicating that production of SP and CGRP by submucosal neurons does not depend on PAF release from epithelial cells (14).ATP is a neurotransmitter in the central and peripheral nervous systems and is also involved in peripheral inflammation and transmission of the sensation of pain (2). Recently, the regulated release of ATP from nonneuronal sources has been shown to play a role in the activation of sensory nerve terminals (2).…”
mentioning
confidence: 99%
“…Moreover, this study demonstrated the activation of TRPV1 by HCl and its enrolment in acid-induced inflammation and contraction of this organ. Capsaicin inhibits the contractions while 5-I-RTX had the opposite effect [33] . The results showed that TRPV1 HCl-induced activation in oesophageal mucosa induce the release of substance P and CGRP release from neurons and PAF release from epithelial cells [33] .…”
Section: Catmentioning
confidence: 95%
“…The study of Cheng et al [33] , identified the presence of TRPV1 in oesophageal mucosa in cats. Moreover, this study demonstrated the activation of TRPV1 by HCl and its enrolment in acid-induced inflammation and contraction of this organ.…”
Section: Catmentioning
confidence: 99%